Basic vision : an introduction to visual perception - Snowden, Robert J.; Thompson, Peter, 1950-; Troscianko, Tom (Oxford University Press, 2012)
Why do things look blurry underwater? Why do people drive too fast in fog? How do you high-pass filter a cup of tea? What have mixer taps to do with colour vision?Basic Vision: An Introduction to Visual Perception demystifies the processes through which we see the world. Written by three authors with over 80 years of research and undergraduate teaching experience between them, it leads the reader step-by-step through the intricacies of visual processing, with full-colour illustrations on nearly every page. The writing style captures the excitement of recent research in neuroscience that has tr.